Effects of sacubitril/valsartan on both metabolic parameters and insulin resistance in prediabetic non-obese patients with heart failure and reduced ejection fraction - Cloro, Cosima; Zaffina, Isabella; Sacchetta, Luca; Arturi, Federico; Clausi, Cristina; Lucà, Stefania; Pelle, Maria Chiara; Giofrè, Federica; Armentaro, Giuseppe; Forte, Valentina; De Rosa, Francesco Mario; Sciacqua, Angela; et al. (Frontiers in Endocrinology, 2022)
Background: The effects of sacubitril/valsartan (sac/val) on metabolic parameters and insulin resistance (IR) in non obese/prediabetic patients, have not been previously described. Aim: To evaluate the effects of sac/val on glycaemic and metabolic parameters, HOMA-IR and echocardiographic parameters in prediabetic patients with HFrEF. Methods: Fifty-nine patients with HFrEF (EF<35%) but without obesity and/or type 2 diabetes mellitus have been enrolled. All the patients at baseline and at weeks 24 underwent complete anthropometrical evaluation, and were subjected to an echocardiogram test. Insulin resistance (IR) has been assessed by HOMA-IR. Results: After 24-week of treatment with sac/val a significant reduction in fasting plasma glucose (109 ± 9 mg/dl vs 103 ± 8 mg/dl, P<0.0001), fasting plasma insulin (16 ± 4 UI/L vs 10 ± 4 UI/L) and HbA1c value (6 ± 0.5% vs 5.3 ± 0.3%, P<0.0001) was observed. Similarly, we observed a significant improvement in IR (HOMA-IR, 4.4 +/- 0.9 vs 2.5 ± 0.6, P<0.0001). The echocardiogram evaluation showed a significant reduction of the left ventricular end-diastolic volume (168 ± 24 vs 158 ± 22 ml, P<0.05), a significant reduction of the left ventricular end-systolic volume (111 ± 26 vs 98 ± 22 ml, P<0.005)and a significant reduction of E/e’ ratio. Sac/val use was also associated with an average 5.1% increase in ejection fraction. Conclusions: Our data seem to indicate that sal/val enhances metabolic control and improves insulin resistance also in prediabetic non obese patients with HFrEF.